PENGARUH WAKTU DAN DOSIS KOMPOS ISI RUMEN SAPI TERHADAP PERTUMBUHAN DAN HASIL TANAMAN KUBIS BUNGA (Brassica oleraceae L.) PADA TANAH GAMBUT (Effect of time and dose compost composting cow rumen contents on growth and yield of cauliflower (Brassica olerasea L.) on peat soil) - man, Sudiran; E. R., Asie,; L., Widiastuti (Universitas Palangka Raya, 2016)
time and dose compost composting cow rumen contents ongrowth and yield of cauliflower (Brassica olerasea L.) on peat soil. Research using a completelyrandomized design (CRD) factorial with two factors. The first factor is the composting time (W)consisting of 3 levels: 15 days, 30 days and 45 days. The second factor is the dose composted cowrumen contents (D), which consists of four levels: 100 g.polybag-1, 200 g.polybag-1, 300 g.polybag-1and 400 g.polybag-1, repeated 4 times to obtain 48 units of trial. The results showed that there was nointeraction effect between time composting and compost dose cow rumen contents on the growth andyield of cauliflower in the peat soil. Time composting 30 days is the best time because it can producestover heaviest weight, ie 335.17 g.plant-1. Composting cow rumen contents at a dose of 400 g.plant-1is the best because it produces a heavy dose of flowers, flower diameter and weight of the heavieststover respectively 114.58 g.plant-1, 9.23 cm and 385.95 g.plant-1.Keywords: composting time, cow rumen compost, peat soil, cauliflower.